Long-term characterization of MRI-morphologic alterations after active motion-compensated liver SBRT: a multi-institutional pooled analysis. (4th March 2023) - Dreher, Constantin; Sarria, Gustavo R.; Miebach, Georgia; Weiss, Christel; Buergy, Daniel; Wojtal, Paulina; Tavakoli, Anoshirwan A.; Krug, David; Oppitz, Hans; Giordano, Frank A.; Both, Marcus; Lohr, Frank; et al.
Abstract: Background: Stereotactic body radiotherapy (SBRT) is an effective therapeutic approach in patients with liver metastases. However, long-term changes in hepatic normal tissue have to be taken into account in multimodal treatment regimes. Magnetic-resonance-imaging (MRI) based morphologic liver alterations (MMA) after liver SBRT have been analyzed longitudinally. Material and methods: 57 patients treated with gantry-based or robotic-based SBRT of 69 treatment volumes of liver metastases, who had long-term follow-up (FU) ≥6 months were included in this retrospective analysis. Post-SBRT MMAs were contoured on each contrast-enhanced-T1-weighted (T1w) MRI-sequence. Morphologic/volumetric data of the liver and MMAs were evaluated longitudinally, including the dependency on treatment-related factors of the planning target volume (PTV) and liver. Results: The median FU time was 1 year [6–48 months]. 66 of 69 treatment volumes developed MMAs (mean 143.8 ± 135.1 ccm at first appearance). 31.8% of MMAs resolved completely during FU. Of the persisting MMAs 82.2%/13.3% decreased/increased in size until last available FU. Morphological characterization of the MMAs at first appearance included 75% hypointense and 25% hyperintense T1w-MRI-based appearances. Hypointense as compared to hyperintense appearance was significantly associated with a higher mean liver dose EQD2α/β=3 Gy ( p = 0.0212) and non-significantly greater MMA size. Variance analysis demonstrated a significant reduction of MMA and total liver volume after SBRT ( p < 0.0001). The volume reduction decelerated longitudinally for both MMA ( p < 0.0001) and liver size ( p = 0.0033). Radiation doses (PTV-BEDα/β=3 Gy and 10 Gy ) were not significantly associated with MMA volume reduction. SBRT of liver metastases with mean liver dose EQD2α/β=3 Gy > 18 Gy were characterized by greater MMA volumes ( p = 0.0826) and steeper MMA reduction gradients during FU than those with EQD2α/β=3 Gy ≤ 18 Gy ( p < 0.0001). Conclusion: Radiogenic MMAs either completely resolve or usually decrease in volume with pronounced reduction during short-term FU. This course was independent of the MMA's morphological appearance. Further, increased mean liver dose was associated with greater MMA size and a greater gradient of MMA size reduction during FU.